MICROBIAL QUALITY ASSESSMENT OF SLICED PINEAPPLE AND WATERMELON SOLD IN SOME SELECTED MARKETS IN KADUNA METROPOLIS, KADUNA STATE. - Madinatu B, Auta K. I.,; H. C, Yayock; B, Solomon (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2017)
Spoilage of fruits which results from the contamination by microorganisms into fruits throughirrigation water, harvesting/processing equipment, improper storage, packaging andtransporting, personal handling, soil, dust and even manure is a source of concern to humanexistence. To assess their microbial quality, sliced fruits sold at some selected markets withinKaduna metropolis were analyzed to determine the microorganism associated with thecontamination. The bacterial mean counts in all the markets for Pineapple and Watermelonranges between 1.5 x 105– 9.5 x105, and 1.4 x 105– 9.9 x 105respectively. The fungal meancount of pineapple and watermelon in the markets ranges from 1.0 x 105– 1.2 x 105and 1.1 x105– 2.0 x 105 respectively. The bacterial isolates were Staphylococcus spp, Escherichiacoli, bacillus spp. While the fungal isolates includes, Aspergillus spp, penicillum, Rhizopus,Fusarium and yeast. The result reveals that the above microorganisms are responsible formicrobial contamination of the fruits sold in the selected markets within Kaduna Metropolis.This therefore calls for serious attention in creating awareness in the control of humaninfectious diseases associated with consumption of contaminated raw fruits within themetropolis.